The clerics of Islam religious authority and political power in Saudi Arabia - Mouline, Nabil; Rundell, Ethan S. (Yale University Press, 2014)
"Followers of Muhammad b. 'Abd al-Wahhab, often considered to be Islam's Martin Luther, shaped the political and religious identity of the Saudi state while also enabling the significant worldwide expansion of Salafist Islam. Studies of the movement he inspired, however, have often been limited by scholars' insufficient access to key sources within Saudi Arabia. Nabil Mouline was granted rare interviews and admittance to important Saudi archives in preparation for this groundbreaking book, the first in-depth study of the Wahhabi religious movement from its founding to the modern day. Gleaning information from both written and oral sources and employing a multidisciplinary approach that combines history, sociology, and Islamic studies, Mouline presents a new reading of this movement that transcends the usual resort to polemics"-- c Provided by publisher